Strategi Content Marketing Berbasis Nilai-Nilai Islam dalam Meningkatkan Reputasi Lembaga Pendidikan Islam di Media Sosial - Fiantini, Irawati; Kunta, Ittaqillah Haitsuma; Hefniy (NAAFI: JURNAL ILMIAH MAHASISWA, 2025)
This study aims to analyze the application of Islamic values-based content marketing strategies in enhancing the reputation of Islamic educational institutions on social media, with a case study at TK Islam Terpadu Permata Kraksaan. This research was conducted to identify how Islamic educational institutions utilize social media to introduce themselves, build their image, and improve their relationship with their audience, particularly parents, by emphasizing the moral and spiritual values contained in Islamic teachings. The method used in this study is a qualitative approach with a case study, where data is obtained through in-depth interviews with the school principal, teachers, and parents, as well as an analysis of social media content published by the institution. The results of the study show that TK Islam Terpadu Permata Kraksaan has successfully utilized social media to convey content that combines academic aspects and the teaching of Islamic values. The content published, such as educational videos, quotations from the Qur'an and Hadith, and documentation of activities, has been proven to increase positive interaction with the audience. However, the challenge faced by this institution is to maintain the consistency of content that is relevant to Islamic values without getting caught up in temporary trends. This study concludes that a content marketing strategy based on Islamic values can significantly enhance the reputation of Islamic educational institutions on social media and strengthen relationships with parents.